The Potential of Glass Fish Chips as One of The Developments in The Toba Regency Culinary Tourism Destination - Wilson, Jerry; Trisnawaty, Trisnawaty; Firani, Sofi (International Journal of Economics and Management, 2024)
Meat Village, located in Tampahan sub-district, Toba regency, North Sumatra, is the center for making ulos weaving type of Ragi Hotang. Almost every house in Meat village is weaving, only a few Meat villagers process fish by frying it and marketing it out of town. The large number of living habitats of glass-glass fish causes a decrease in the population of pora-pora. The residents in the meat village and its surroundings cannot process the glass fish because it has hard thorns. For this reason, the author examines whether pora-pora fish can be processed and used as souvenirs typical of Toba Regency using qualitative research methods. And based on the results of experiments that have been done, glass fish can be processed into chips with the right standard recipes and procedures. Glass fish chips have a savory taste and crumbly texture. This glass fish can be consumed by residents, and can be marketed in Toba district. It can be as a snack or souvenir by visitors, considering that this type of snack can last a long time.